CENGKOK GENDERAN DUALOLO SEBAGAI SUMBER IDE PENCIPTAAN KOMPOSISI MUSIK “FANTASIA FROM DUALOLO” KARYA : PURWA ASKANTA - Purwa Askanta; Danis Sugiyanto (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2021)
This journal is entitled "Cengkok Genderan Dualolo as a Source of Ideas for the Creation of Fantasia From Dualolo Music Composition" by Purwa Askanta. The focus of the problems studied in this paper includes the analysis of musical composition works that use the source of artistic ideas from a dualolo genderan twist in Javanese Karawitan. How the idea is used as a theme and developed to form a sound building in the form of Fantasia in three parts. In this composition, there are several creation systems that need to be expressed in order to understand the reader in order to understand the concept of creating this musical work. The method used in this journal is descriptive analysis with a form of music analysis approach. The findings of this research will show creativity in composing a new musical composition by Purwa Askanta. Meanwhile, the purpose of this research is to contribute in the form of techniques and methods of creating musical works that raise a simple idea from elements of the Javanese musical tradition in the form of the dualolo gendered twisted. It is hoped that the writings in this journal can broaden the readers' insight and become a reference for those who explore the creation of musical works.